2019
DOI: 10.1021/acs.macromol.9b02021
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Asymmetric Leaf-Shaped Crystals in Ultrathin Films of Oriented Polyethylene Molecules Resulting from High-Temperature Relaxation and Recrystallization

Abstract: We melted, annealed, and recrystallized ultrathin films of oriented polyethylene (PE) molecules prepared by melt-drawing. A large number of randomly oriented asymmetric leaf-shaped crystalline structures consisting of preferentially oriented lamellae were formed simultaneously, as observed by optical and atomic force microscopies. The structural arrangement within these leaf-shaped crystalline structures was identified by grazing incidence X-ray diffraction. These structures consisted of two distinct sections,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…Crystallization in PCL films of thickness t = 200–300 nm and PESu films of thickness <1 μm lead to a fern-like dendritic assembly, with the main stalks being composed of flat-on lamellae and the side branches being an alternate combination of flat-on and edge-on ones. , An ultrathin PE film reportedly also results in a sea-weed shape ( i.e. , fern-like geometry) crystal-assembly morphology upon long-time annealing at specific temperatures . Mareau and Prud’homme observed that the crystal growth rate of PCL edge-on lamellae is 15 times faster than that of the flat-on ones, and this fact may suggest that the lamellae in alternate ridge/valley bands do not grow uniformly as a helix continuously twists, but the growth may be intermittent and crystal packing can be discontinuous.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Crystallization in PCL films of thickness t = 200–300 nm and PESu films of thickness <1 μm lead to a fern-like dendritic assembly, with the main stalks being composed of flat-on lamellae and the side branches being an alternate combination of flat-on and edge-on ones. , An ultrathin PE film reportedly also results in a sea-weed shape ( i.e. , fern-like geometry) crystal-assembly morphology upon long-time annealing at specific temperatures . Mareau and Prud’homme observed that the crystal growth rate of PCL edge-on lamellae is 15 times faster than that of the flat-on ones, and this fact may suggest that the lamellae in alternate ridge/valley bands do not grow uniformly as a helix continuously twists, but the growth may be intermittent and crystal packing can be discontinuous.…”
Section: Introductionmentioning
confidence: 96%
“…16,17 An ultrathin PE film reportedly also results in a sea-weed shape (i.e., fern-like geometry) crystal-assembly morphology upon long-time annealing at specific temperatures. 18 Mareau and Prud'homme 19 observed that the crystal growth rate of PCL edge-on lamellae is 15 times faster than that of the flat-on ones, and this fact may suggest that the lamellae in alternate ridge/valley bands do not grow uniformly as a helix continuously twists, but the growth may be intermittent and crystal packing can be discontinuous. Duan et al 20 (2004) observed a nonbirefringence ring in 100−300 nm-thick iPS films, and based on the atomic force microscopy (AFM) results, the rhythmic growth/precipitation model was proposed, and they claimed that this proposed model appropriately matched with polyester thin films ≤850 nm.…”
Section: ■ Introductionmentioning
confidence: 99%
“…While, in domain B, the lamellae are densely packed with fewer facets exposed, and its height curve is a regular zigzag along the tangential direction. Therefore, it is concluded that domain B is composed of inclined terrace-like lamellae 34 caused by tilted lamellae rather than dense multilayered flat-on lamellae. Besides, there is a transition region at the junction of the two lamellae, which is relatively low in height and has a certain bending phenomenon along the radial direction.…”
Section: Spherulitic Morphology and Its Lamellarmentioning
confidence: 97%
“…Highly oriented PLLA and PDLA thin films were prepared according to the melt-draw technique, which has been frequently used for getting highly oriented ultrathin films. During the melt-draw procedure, a small amount of 0.6 wt % polymer solution in DMF was first poured on a preheated glass plate at specified temperatures ranging from 152 to 180 °C and spread uniformly by a glass rod. After evaporation of the DMF solvent, the thin molten polymer layer was then picked up by a motor-driven cylinder with a draw speed ranging from 5 to 45 cm/s.…”
Section: Experimental Sectionmentioning
confidence: 99%